Les Technopères : la carte informatique, un chemin initiatique - Eric Villagordo (ReS Futurae)
The eight-parts saga of the comic strip Les Technopères (1998-2006) by Jodorowsky, Beltran and Janjetov depicts a rich representation of computer science in the beginning of the story. Inspired by a cyberpunk background, the story can be read, on the one hand, as a parabola of computer science as a new system of possible, a new geography of adventure and on the other hand, as a totalitarian system of control. Two categories of representation can be seen : inside the computer and inside the connected cyberspace. We will try to identify the aesthetic and narrative devices which permit us to represent what is not representable, the ubiquitous computer science, the hyperconnection, the abolition of time and space as well as the infinitely small inside the machines. The confusion of this hyperspace, with a limited inside as well as an outside totally growing, is a challenge for the plastic artists, Beltran and Janjetov. Thanks to the hybridization of traditional and digital graphic techniques, but also thanks to the specificity of solidary pictures (Groensteen, 1999) in comic strip, this graphic narrative shows us practical and significant representations of computer science. The sequential art of comic strip offers us a space organization of the cyberspace hardly representable.